Present Bias Unconstrained: Consumption, Welfare, and the Present-Bias Dilemma - Peter Maxted (The Quarterly Journal of Economics, 2025)
Abstract By augmenting the continuous-time specification of Harris and Laibson (2013) with the assumption that hard borrowing constraints do not bind in equilibrium, present bias can be tractably incorporated into rich consumption-saving models featuring stochastic income, risky and illiquid assets, and costly borrowing. I present closed-form expressions characterizing how present bias affects consumption, illiquid asset demand, and welfare. This welfare analysis specifies the channels through which present bias can matter for policy and uncovers the present-bias dilemma: present bias can have large welfare costs, but individuals have little ability to alleviate these costs using financial commitment devices like illiquid assets.